The Effect of Interest Rate Caps on Bankruptcy: Synthetic Control Evidence from Recent Payday Lending Bans - Kabir Dasgupta; Brenden J. Mason (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2019)
Citing consumer protection concerns, New Hampshire – along with three other states – recently banned payday lending by implementing an APR cap on small loans. New Hampshire presents a compelling quasi-experiment: its neighbors already had a payday loan ban inplace. Hence, New Hampshire consumers were completely shut out of the storefront payday loan market. We perform a synthetic control analysis for all four of the recently-banning states. Our results show that, on the aggregate, bankruptcies are largely unaffected by the bans. Our New Hampshire results are characterized by an initial rise in bankruptcies after the ban, followed by a fall. This is consistent with the notion that payday bans hurt credit-constrained consumers in the short-run, but could help them in the long-run. We also analyze survey data of payday borrowers and find that while bankruptcies are unaffected, consumers substitute toward paying their credit card bills late and using pawnshops.
Keywords: G23; G28; D12; C13; 330; interest rate cap; payday lending; credit rationing; bankruptcy; informal bankruptcy; synthetic control; ArCo